Mer des Caraïbes et paysages du commerce illégal : les routes de la contrebande entre les îles, les baies et le réseau hydrographique des Juifs et des nouveaux ChrétiensTT - - Cwik, Christian (1970-...) (Université des Antilles (2015-....), 2019)
The majority of maritime trade within the Caribbean has been based on smuggling since the beginning of European influenced trade in this area. With the establishment of Non-Iberian colonies such as English, French, Dutch, German and Danish during the 17th century also Jewish merchants seeped into the illegal markets with sugarcane, tobacco, slaves, salt, vanilla etc. This lecture would like to highlight the illicit networks of Jewish and New Christian traders based on their clandestine Caribbean routes by means of Braudelian methods during 1670 and 1730. Seemingly insignificant ports and coastal communities as well as bays have become global cargo hubs due to these extensive networks. The majority of these places have been located in the Caribbean Frontier, which has been often dominated by Indians, escaped slaves, refugees, pirates and other outlaws. The role of Jews as middlemen between legal and illegal trade will be another focus of this lecture.